2019
DOI: 10.1186/s41182-019-0143-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescription for under-fives with common cold or upper respiratory tract infection in Savannakhet Province, Lao PDR

Abstract: Background The irrational use of antibiotics has been identified as a major problem in healthcare, and it can lead to antimicrobial resistance, treatment failure, and increased healthcare costs. Although many studies worldwide have focused on the irrational use of drugs, reports on prescription practice in Lao PDR remained limited. This study aimed to examine the patterns of antibiotic prescription for under-fives with common cold or upper respiratory tract infection (URTI) at pediatric outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The rational use of medicines occurs when a correctly selected medicine is prescribed for appropriate indications, in doses that meet their own individual requirements, for an adequate period of time, at the lowest cost for both the patients and the society [ 4 ]. Several studies have shown that inappropriate antibiotic use is widespread across the globe [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rational use of medicines occurs when a correctly selected medicine is prescribed for appropriate indications, in doses that meet their own individual requirements, for an adequate period of time, at the lowest cost for both the patients and the society [ 4 ]. Several studies have shown that inappropriate antibiotic use is widespread across the globe [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous children with ARI and diarrhea are treated with antibiotics. However, in these cases, antibiotic treatment may not be required [68]. Previous studies have shown that the use of antibiotic was associated with higher rates of resistance in children [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobials were prescribed for between 45% and 70% of inpatients in Lao hospitals from 2004 to 2018. [57][58][59][60] Doctors stated that they mainly prescribed antibiotics according to the National Standard Treatment Guidelines (STG), advice from their peers or from more experienced colleagues. 57 Until recently these guidelines have not included detailed recommendations for antimicrobial prescribing for the diversity of Lao infectious diseases, but detailed MoH antimicrobial guidelines have now been released.…”
Section: Amu In Humansmentioning
confidence: 99%
“…First-line antibiotics based on Lao National STG (amoxicillin, ampicillin, erythromycin and penicillin V) were the most commonly prescribed. 60 A large survey in Salavan Province between 2017 and 2018 revealed that among 796 participants from communities, 39% claimed that they used antibiotics during their previous illness and 22% admitted that they used antibiotics without indications or from informal sources. 63 'Ampi' or ampicillin was the most commonly mentioned antibiotic, by 76% of 775 survey participants, and wound treatment (44%) was the main reason for antibiotic use in Salavan in the same period.…”
Section: Amu In Humansmentioning
confidence: 99%